Distinct capacity for differentiation to inner ear cell types by progenitor cells of the cochlea and vestibular organs - McLean, Will J. (Development, 2016)
Disorders of hearing and balance are most commonly associated with damage to cochlear and vestibular hair cells or neurons. Although these cells are not capable of spontaneous regeneration, progenitor cells in the hearing and balance organs of the neonatal mammalian inner ear have the capacity to generate new hair cells after damage. To investigate whether these cells are restricted in their differentiation capacity, we assessed the phenotypes of differentiated progenitor cells isolated from three compartments of the mouse inner ear – the vestibular and cochlear sensory epithelia and the spiral ganglion – by measuring electrophysiological properties and gene expression. Lgr5(+) progenitor cells from the sensory epithelia gave rise to hair cell-like cells, but not neurons or glial cells. Newly created hair cell-like cells had hair bundle proteins, synaptic proteins and membrane proteins characteristic of the compartment of origin. PLP1(+) glial cells from the spiral ganglion were identified as neural progenitors, which gave rise to neurons, astrocytes and oligodendrocytes, but not hair cells. Thus, distinct progenitor populations from the neonatal inner ear differentiate to cell types associated with their organ of origin.